Prestasi Belajar dan Perilaku Keagamaan Siswa - Haizatul Masnaiyah (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
This paper aims to: determine student achievement, student religious behavior relationship between learning achievement with student religious behavior. Students sampled is 87 students. The technique of collecting data using questionnaires and documentation. While the methods of analysis used is using the technique Spearman correlation analysis Tata offer. The results showed that (1) Achievement Student achievement is quite good, reaching an average value of 82.7. (2) Religious behavior of students classified as good ie with a percentage of 56.3% good, 39.1% moderate, 2.3% and 2.3% splendidly less. (3) There is a significant relationship between academic achievement by religious behavior of students with the level of strength of the relationship between the two moderate. This is based on the results of data calculated by the formula Spearman using IBM SPSS Statistics program version 22, which shows the correlation between the variables x and y variables amounted to 0,404 with the Sig. (2-tailed) = 0,000.